INTERAKSI MANUSIA DAN AI: MEMBANGUN HUBUNGAN YANG BERKELANJUTAN - Nurvitian, Adedayesa; Fitaloka, Fahira; Nur Janah, Anisa; Sukmawati, Adelia Dwi (LPPM Politeknik Pajajaran ICB Bandung, 2024)
Rapid advances in artificial intelligence have opened up new opportunities for improved interactions between humans and machines. This study explores the various dynamics associated with the human-AI relationship, ranging from technical to ethical aspects. The aim of this research is to understand how harmonious collaboration between humans and AI can be established and sustained in the long term. It also highlights the important role of massive AI socialization and societal acceptance in creating a mutually supportive symbiosis. Through descriptive methods, this research provides deep insights into the implications of these interactions and offers recommendations to facilitate a sustainable relationship between humans and AI. Keywords: Interactions, Artificial Intelligence, Human, Machine, Collaboration